Pancasila, HAM, dan Demokrasi di Era Globalisasi: Antara Idealisme dan Realitas di Tanah Papua - Rama Gardika (Jurnal Ilmiah Mimbar Demokrasi, 2025)
This study aims to examine the implementation of freedom of expression and democracy in Papua, with particular emphasis on the structural, social, political, and cultural challenges that shape the region’s democratic quality. A qualitative approach was employed through an extensive literature review and document analysis, encompassing statutory regulations, official state reports, academic publications, and media coverage. The findings reveal that, although Indonesia’s legal framework guarantees freedom of expression as an integral part of human rights, its realization in Papua faces multiple barriers, including limited access to information, persistent tensions between security forces and local communities, and perceived injustices in development policies and resource management. Political discourse is often polarized, reinforced by ethnic identity dynamics and a history of conflict, thereby constraining the climate for civil liberties. The study concludes that enhancing democratic quality in Papua requires a multidimensional strategy, encompassing stronger civil rights protection, government transparency, inclusive development, and participatory dialogue mechanisms. These findings underscore the need for coordinated efforts among the central government, local authorities, civil society, and the international community to secure a substantive and equitable democracy in Papua.